The Case of Shougang: Comparing Chinese and Western Mining in Peru - Amos, Irwin (2013)
Observers have expressed concern that Chinese mining  companies operating  in Latin America are violating  labor and environmental standards to a greater extent than other foreign mining companies. Critics point to one operation in particular  –Shougang Hierro  Peru– as evidence of China’s threat to Latin America’s workers and environment. Indeed, Shougang has experienced a far higher rate of strikes than other foreign firms. Many observers have assumed that Shougang’s strike problem stems from an inevitable culture clash between Peruvian unions and Chinese management. In fact, union relations remained positive for years, until Shougang lost funding when its parent company suffered a crisis back in China in 1995. I argue that the strike problem stems largely from Shougang’s response to its 1995 funding crisis: it burnt its bridges with the unions to save money. Some have suggested instead that Shougang has suffered more strikes because it has a far worse record on labor safety and environmental protection. In fact, new Peruvian government data show that Shougang’s labor and environmental  record is not significantly worse than that of other foreign firms. The most similar American firm, Doe Run Peru, has fewer union problems despite worse labor and environmental standards. I argue that Doe Run Peru has maintained better labor relations by careful communication with its unions. This study refutes the idea that Shougang suffered from an inevitable China-Peru culture  clash and highlights the importance of open dialogue with organized labor.